Towards a Healthy Aging: A Systematic Review about Music and Physical Exercise as Modulating Factors - Diaz Abrahan, Veronika (2019)
Aging is defined as a set of biological processes genetically determined, that are characterized by the manifestation of gradual and progressive cognitive deterioration. Currently, there is a strong interest to identify which factors promote healthy cognitive aging, and the interventions and strategies that protect against age-related neurodegenerative diseases. The aim of this systematic review is to outline non-pharmacological interventions that included music or physical activity programs for older adults. Studies published between the years of 2007 and 2018 in major databases (Redalyc, Scielo, Science Direct, PubMed, Taylor, & Francis) were included in this review, obtaining 34 empirical articles (17 related with music and 17 with physical activity). The main conclusion is that an enhanced cognitive performance is found in older adults who were exposed to these interventions.